Contribution of gut microbiota toward renal function in sepsis - Xu, Yaya; Kong, Xiangmei; Zhu, Yueniu; Xu, Jiayue; Mao, Haoyun; Li, Jiru; Zhang, Jianhua; Zhu, Xiaodong (Frontiers in Microbiology, 2022)
Sepsis most often involves the kidney and is one of the most common causes of acute kidney injury. The prevalence of septic acute kidney injury has increased significantly in recent years. The gut microbiota plays an important role in sepsis. It interacts with the kidney in a complex and multifactorial process, which is not fully understood. Sepsis may lead to gut microbiota alteration, orchestrate gut mucosal injury, and cause gut barrier failure, which further alters the host immunological and metabolic homeostasis. The pattern of gut microbiota alteration also varies with sepsis progression. Changes in intestinal microecology have double-edged effects on renal function, which also affects intestinal homeostasis. This review aimed to clarify the interaction between gut microbiota and renal function during the onset and progression of sepsis. The mechanism of gut–kidney crosstalk may provide potential insights for the development of novel therapeutic strategies for sepsis.